Cell-line and culture model specific responses to organic contaminants in house dust: cell bioenergetics, oxidative stress, and inflammation endpoints - Dos Santos, Mauricius Marques (2023)
Exposure to organic contaminants in house dust is linked to the development or exacerbation of many allergic and immune disorders. In this work, we evaluate the effects of organic contaminants on different cell bioenergetics endpoints using five different cell lines (16HBE14o-, NuLi-1, A549, THP-1 and HepG2), and examine its effects on lung epithelial cells using conventional 2D and 3D (air-liquid interface/ALI) models. Proposed rapid bioenergetic assays relies on a quick, 40 min, exposure protocol that provides equivalent dose-response curves for ATP production, spare respiratory capacity, and cell respiration. Although cell-line differences play an important role in assay performance, established EC50 concentrations for immortalized lung epithelial cells ranged from 0.11 to 0.15 mg/mL (∼2 µg of dust in a 96-well microplate format). Bioenergetic response of distinct cell types (i.e., monocytes and hepatocytes) was significantly different from epithelial cells; with HepG2 showing metabolic activity that might adversely affect results in 24 h exposure experiments. Like in cell bioenergetics, cell barrier function assay in ALI showed a dose dependent response. Although this is a physiologically relevant model, measurements are not as sensitivity as cytokine profiling and reactive oxygen species (ROS) assays. Observed effects are not solely explained by exposure to individual contaminants, this suggests that many causal agents responsible for adverse effects are still unknown. While 16HBE14o- cells show batter barrier formation characteristics, NuLi-1 cells are more sensitivity to oxidative stress induction even at low house dust extract concentrations, (NuLi-1 2.11-fold-change vs. 16HBE14o- 1.36-fold change) at 0.06 µg/mL. Results show that immortalized cell lines can be a suitable alternative to primary cells or other testing models, especially in the development of high-throughput assays. Observed cell line specific responses with different biomarker also highlights the importance of careful in-vitro model selection and potential drawbacks in risk assessment studies.